Diversity and Inter-Connections in the CXCR4 Chemokine Receptor/Ligand Family: Molecular Perspectives - Pawig, Lukas; Klasen, Christina; Weber, Christian; Bernhagen, Jürgen; Noels, Heidi (Frontiers in Immunology, 2015)
CXCR4 and its ligand CXCL12 mediate the homing of progenitor cells in the bone marrow and their recruitment to sites of injury, as well as affect processes such as cell arrest, survival and angiogenesis. CXCL12 was long thought to be the sole CXCR4 ligand, but more recently the atypical chemokine macrophage migration inhibitory factor (MIF) was identified as an alternative, non-cognate ligand for CXCR4 and shown to mediate chemotaxis and arrest of CXCR4-expressing T-cells. This has complicated the understanding of CXCR4-mediated signaling and associated biological processes. Compared to CXCL12/CXCR4-induced signaling, only few details are known on MIF/CXCR4-mediated signaling and it remains unclear to which extent MIF and CXCL12 reciprocally influence CXCR4 binding and signaling. Furthermore, the atypical chemokine receptor ACKR3 (previously CXCR7) has added to the complexity of CXCR4 signaling due to its ability to bind CXCL12 and MIF, and evoke CXCL12- and MIF-triggered signaling independently of CXCR4. Also, extracellular ubiquitin (eUb) and the viral protein gp120 (HIV) have been reported as CXCR4 ligands, whereas viral chemokine vMIP-II (Herpesvirus) and human beta-defensin 3 (HBD-3) have been identified as CXCR4 antagonists. This review will provide insight into the diversity and inter-connections in the CXCR4 receptor/ligand family. We will discuss signaling pathways initiated by binding of CXCL12 vs MIF to CXCR4, elaborate on how ACKR3 affects CXCR4 signaling and summarize biological functions of CXCR4 signaling mediated by CXCL12 or MIF. Also, we will discuss eUb and gp120 as alternative ligands for CXCR4, and describe vMIP-II and HBD-3 as antagonists for CXCR4. Detailed insight into biological effects of CXCR4 signaling und underlying mechanisms, including diversity of CXCR4 ligands and inter-connections with other (chemokine) receptors, is clinically important, as the CXCR4 antagonist AMD3100 has been approved as stem cell mobilizer in specific disease settings.